Music as expression of children’s spirituality: the case of Steiner early childhood education - Boland, Neil (International journal of children's spirituality, 2025)
This article examines early childhood music education from the perspective of Rudolf Steiner’s indications for music with young children, exploring their connection to his concepts of childhood spirituality. Specifically, it looks at how the musical interval of the fifth relates to the spirituality of young children. It investigates music practices in Steiner early childhood settings and considers whether Steiner’s ideas of music and soul health, live performance and ritual have broader applicability beyond Steiner environments. Since its inception in 1926, Steiner early childhood education has expanded to approximately 80 countries, reflecting an enduring relevance of Steiner’s ideas. As the centenary approaches, this article revisits Steiner’s approach to music education for young children, emphasising its unique reflection of child spirituality. While Steiner education is renowned for attributes such as play, imagination, and the use of natural materials, its distinctive approach to music, particularly its links to child spirituality, remains underexplored.